Effect of a Health Education Intervention on Physical Activity Knowledge, Attitude and Behavior in Health Volunteers - R Seyed Emami; H Eftekhar Ardebili; B Golestan (Tehran University of Medical Sciences, 2011)
Background & Objective: Regular and adequate physical activity is a major factor in maintaining good health throughout entire life course. Levels of inactivity are high in all countries. Effective educational interventions are needed to promote physical activity in all populations. The aim of this study was to determine the effect of a heath education intervention on physical activity knowledge, attitude, and behavior in health volunteers of Tehran in 2008. Methods & Materials: All active female health volunteers of Tehran, district 14 (n=100) were recruited for this experimental study. Data were gathered using a questionnaire of knowledge, attitude, and behavior regarding physical activity. The questionnaire was completed by all participants in two phases of pre- and post-intervention (four weeks after the intervention). Health education intervention strategies were presented to the intervention group during three educational sessions with one week interval between the sessions. Data were analyzed using related statistical tests. Results: Findings showed significant statistical differences in knowledge, total physical activity rate per week, and the mean sitting time per day between the control and intervention groups after the intervention (P<0.05). While, these variables were not significantly different before the educational intervention among both groups. Conclusion: The health education intervention presented in this study was effective in promoting knowledge, total physical activity rate per week, and mean sitting time per day among the female health volunteers.